The electromembrane extraction of pharmaceutical compounds from animal tissues - Bavlovič Piskáčková, Hana; Kollárová-Brázdová, Petra; Kučera, Radim; Macháček, Miloslav; Pedersen-Bjergaard, Stig; Štěrbová-Kovaříková, Petra (Analytica chimica acta, 2021)
The reliable analysis of various compounds from tissue requires a tedious sample preparation. The sample pretreatment usually involves proper homogenization that facilitates extraction of target analytes, followed by an appropriate sample clean-up preventing matrix effects. Electromembrane extraction (EME) seems to have a significant potential to streamline the whole procedure. In this study, the applicability of EME for direct isolation of analytes from animal tissues was investigated for the first time. Extraction conditions were systematically optimized to isolate model analytes (daunorubicin and its metabolite daunorubicinol) from various tissues (myocardium, skeletal muscle and liver) coming from a pharmacokinetic study in rabbits. The relative recoveries of daunorubicin and its metabolite in all tissues, determined by the UHPLC-MS/MS method, were higher than 66 and 75%, respectively. Considerably low matrix effects (0 ± 8% with CV lower than 6%) and negligible content of phospholipids detected in EME extracts demonstrate the exceptional effectiveness of this microextraction approach in purification of tissue samples. The difference in the concentrations of the analytes determined after EME and reference liquid-liquid extraction of real tissue samples was lower than 12%, which further emphasized the trustworthiness of EME. Moreover, the considerable time reduction needed for sample treatment in case of EME must be emphasized. This study proved that EME is a simple, effective and reliable microextraction technique capable of direct extraction of the analytes from pulverized tissues without the need for an additional homogenization or purification step.
Keywords: Tissue; Tandem Mass Spectrometry; Electromembrane extraction; Membranes, Artificial; tandemová hmotnostní spektrometrie; fosfolipidy; Phospholipids; Anthracyclines; králíci; Pharmaceutical Preparations; Rabbits; membrány umělé; Sample treatment; Microextraction; Homogenization; zvířata; Animals; léčivé přípravky